Perilaku Konsumtif Mahasiswa UIN Sunan Gunung Djati Bandung dalam Menggunakan Aplikasi Online Food Delivery (OFD) Secara Implusif - Anjani, Sakila Meila; Rahmawati, Nurul; Oktiani, Rashifah Zahra; Hanina, Savira; Anggraeni, Sri lestari; Pangestu, Trimas Arya; Wardiyah, Mia Lasmi (Melati Institute, 2024)
Online Food Delivery (OFD) service is a food delivery service that allows online transactions via an application. This application is very popular among students, including at UIN Sunan Gunung Djati, because it makes access easy and offers a variety of food choices. This research was conducted to understand the consumer behavior of students who use the OFD application. The method used is an online survey with quantitative techniques and qualitative descriptive analysis. The research sample consisted of 113 semester II-VI student respondents aged 19-23 years. The research results show that there is a significant correlation between the behavior of excessive use of social media Online Food Delivery (OFD) and the consumptive lifestyle of students. Almost half of the respondents (51.3%) stated that Online Food Delivery (OFD) plays a positive and significant role in consumptive behavior. The main factors that encourage the use of OFD include practicality, attractive promos, and inviting friends to try viral foods.